2010
DOI: 10.1002/hrm.20331
|View full text |Cite
|
Sign up to set email alerts
|

Getting the most from MBA internships: Promoting intern learning and job acceptance

Abstract: MBA internships are commonly used for training and recruiting management talent. Yet, research overlooks what makes them effective. A longitudinal study investigates the relationships that goal clarity, autonomy, and prior experience have with MBA intern learning and job acceptance intentions. Results show learning partially mediates the relationship of goal clarity to job acceptance intentions, and that less experienced MBA interns learn more under conditions of high goal clarity and low autonomy (i.e., when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 47 publications
(62 reference statements)
3
59
0
Order By: Relevance
“…Educational researchers have discovered linkages between goal clarity and student learning in the classroom environment (Seidel, Rimmele, and Prenzel 2005). In a study focused on MBA interns, Beenen and Rousseau (2010) showed that goal clarity was positively related to intern learning and job pursuit behaviour.…”
Section: Task Goal Claritymentioning
confidence: 99%
See 2 more Smart Citations
“…Educational researchers have discovered linkages between goal clarity and student learning in the classroom environment (Seidel, Rimmele, and Prenzel 2005). In a study focused on MBA interns, Beenen and Rousseau (2010) showed that goal clarity was positively related to intern learning and job pursuit behaviour.…”
Section: Task Goal Claritymentioning
confidence: 99%
“…Task goal clarity refers to understanding the work products that are expected and the standards by which those products will be evaluated (Beenen and Rousseau 2010). Because of the short-term nature of internships, it is important for interns to quickly understand their roles in terms of task goals.…”
Section: Task Goal Claritymentioning
confidence: 99%
See 1 more Smart Citation
“…The current paper views all internship formats as structured student learning experiences (Beenen and Rousseau, 2010) that should enable students to transition from formal classroom learning into the predominantly informal and/or accidental learning environment of contemporary workplaces (Candy and Crebert, 1991). To master this transition successfully, internships should be specifically designed to support students in the development of cognitive, skill-based and affective learning outcomes (Kraiger et al, 1993).…”
Section: Students' Internship Learning Experiencementioning
confidence: 99%
“…The current paper defines internships as temporary (non-permanent) work placements that reflect a period of transition from higher education to employment. As a result, internships are defined as student learning experiences focused on applying classroom knowledge in practical situations (Beenen and Rousseau, 2010). Within the internship arena, learning experiences may be grouped into traditional internships and CMIs, which encompass simulated internships and e-internships.…”
Section: Computer-mediated Internships (Cmis)mentioning
confidence: 99%